Acute phacomorphic glaucoma in patient with diabetes mellitus type 1 – case report - Chomańska, Urszula; Kraśnicki, Paweł; Proniewska-Skrętek, Ewa; Mariak, Zofia (Klinika Oczna / Acta Ophthalmologica Polonica, 2010)
Diabetes mellitus contributes to an earlier and a quicker development of opacities of the lens and worsening of the vision in affected people, in comparison with healthy people in similar age. The main source of energy in the human lens is glucose, which is metabolised through the glycolytic process. When the level of glucose increases in blood, its content also increases in aqueous humour and in the lens. It causes a saturation of the glycolytic process and the activation of the sorbitol pathway with participation of aldose reductase. The accumulation of sorbitol is responsible for the growth of osmotic pressure inside the lens, inflow of water and gradual swelling of its fibres. In extreme cases a swelling of the lens can even lead to occurrence of cataracta intumescens and secondary glaucoma. The primary treatment of cataracta intumescens is to remove lens surgicaly, preferably after lowering intraocular pressure. In that report is presented a particular case of such, fulminating course of ophthalmological complications in patient with diabetes mellitus type 1.